Big eyes [videorecording (DVD)] - Adams, Amy; Waltz, Christoph, 1956-; Huston, Danny, 1962- (Anchor Bay Entertainment, 2015)
Walter Keane became a worldwide celebrity and talk show fixture in the 1950s after he pioneered the mass production of prints of big-eyed kids, and used his marketing savvy to sell them cheaply. Unfortunately, he claimed to be the artist. That role was played by Margaret, his shy wife. The ruse broke up their marriage and led to a divorce and a dramatic courtroom battle to prove authorship of the paintings.